Your undergraduate degree in psychology : from college to career - Hettich, Paul I. (SAGE Publications, 2014)
This text provides innovative strategies and tools for succeeding after college with an undergraduate degree in psychology. Drawing on current research data, applied theory, and both academic and workplace experiences, it helps stimulate self-reflection and improve decision making as students approach their careers. The text covers key topics in the college-to-career transition, including career planning and development, understanding what employers want and do not want, coping with personal life changes, becoming a valued employee, and more.